Development Plan for a Tourism Area Based on Education and Local Wisdom in the Mandeh Area, South Pesisir, Indonesia - Ahmad Rivauzi; Wirdati Wirdati; Rido Putra; Rengga Satria; Siti Fatimah; Halomoan Halomoan; Muhamad Yusuf; Isma Darma Yanti (Jurnal Kawakib, 2025)
This article focuses on development plans through education and local wisdom in the Mandeh Tourism Area, South Pesisir Regency, Indonesia. The research methods used in this study were desk study, participatory qualitative method through focus group discussions (FGD), and direct observation at the research site. The results of this study describe several points, namely: an analysis of the empowerment and local wisdom of the Mandeh Nagari community, and an analysis of the development potential of the Mandeh Tourism Area. The recommendation from this study is that education and empowerment of local wisdom are very strategic in encouraging the growth and sustainability of the Mandeh area as a leading tourist destination that provides greater benefits in terms of culture and economic perspective and must involve the active participation of the community, the private sector, the central government, the regional government, and the Nagari government.